In VitroEvaluation of Anticancer Activity for Novel Family of Synthetic Copper/Polyamines Complexes - Bayan Mustafa Mohammad Mansour (My University, 2015)
The cancer mortality and morbidity rate is rising all over the world in developed countries and in developing ones which make cancera major health problem. Many researches and efforts have been made in order to cure cancer, stop its spread or even to contain its damage. Chemotherapy is widely used to treat cancer but its side effects and toxicity are a major concern. One of the most significant discoveries in cancer chemotherapy is cisplatin which is very effective in treating different types of cancer especially testicular cancer which has a cure rate exceeds 90%. However, the treatment is limited because of several side effectsin addition to inherit and acquired resistance that limits its usage too. These drawbacks have motivated extensive search for other active antitumor metal- based complexes with improved pharmacological properties. This study investigates the anticancer activity of copper polyamines complexes. Seven complexes were prepared and screened in vitro for both cytotoxic and cytostatic activities against four cell lines (human muscle cells as normal control: L6 cell line, colon cancer: Hct cell line, prostate cancer: PC3 cell line and liver cancer: HepG2 cell line) using MTT test. Results shows that complex 1 and complex 3 induced cytotoxic effect on Hct (IC50: 0.03, 0.015), PC3 (IC50: 0.02, 0.015) and HepG2 (IC50: 0.015, 0.015) cell lines at nontoxic level compared to its effect on L6 cell line (IC50: 0.07). Also complex 7 induced cytotoxic effect on HepG2 cell line (IC50: 0.07) at nontoxic level compared to its effect on L6 cell line (IC50: 0.09). However, for cytostatic effect complex 1 and complex 3 induced cytostatic effect on PC3 and HepG2 (IC50: 0.015) cell lines at nontoxic level compared to its effect on L6 cell line (IC50: 0.02), also complex 4 and complex 5 induced cytostatic effect on HepG2 cell line (IC50: 0.13, 0.09) at nontoxic level compared to its effect on L6 cell line (IC50: 0.18, 0.1). These complexes exhibited promising antiproliferative activity against tested cell lines which indicates that these complexes have anticancer effect at nontoxic concentrations.

ان معدلات الإصابة والوفيات الناتجة عن مرض السرطان في تزايد مستمر في جميع أنحاء العالم سواء في الدول النامية والمتقدمة على حد سواء ما يجعل من السرطان مشكلة صحية عالمية كبيرة. لقد قدمت الكثير من الأبحاث والجهود من اجل علاج السرطان أو وقف انتشاره أو حتى التقليل من أضراره. يستخدم العلاج الكيميائي على نطاق واسع لعلاج السرطان ولكن تبقى أثاره الجانبية والسمية مصدر قلق كبير. يعد السيسبلاتين احد أهم الاكتشافات في العلاج الكيميائي للسرطان حيث اثبت فعاليته في القضاء على أنواع مختلفة من السرطان وخاصة سرطان الخصية حيث يتعدى معدل الشفاء 90%. ومع ذلك فان العلاج بالسيسبلاتين تحده العديد من الآثار الجانبية بالإضافة للمقاومة الموروثة والمكتسبة للعلاج. هذه العقبات وغيرها شجعت في زيادة الأبحاث عن مركبات تعتمد على معادن أخرى تكون نشطة في مقاومة الخلايا السرطانية وذات خصائص دوائية محسنة. تبحث هذه الدراسة في المركبات المكونة من النحاس المرتبط بالامينات متعددة المنح ومدى فاعليتها في تثبيط الخلايا السرطانية. تم اختيار سبع مركبات من اجل فحص تأثيرها على السرطان وذلك بتعريض ثلاثة أنواع من الخلايا السرطانية (القولون, البروستاتا والكبد) لتراكيز متزايدة من تلك المركبات ومن ثم استخدام صبغة MTT لفحص مدى سمية هذه المركبات كما تم استخدام خلايا سليمة كمجوعة ضابطة للاختبار (خلايا عضلية هيكلية). أظهرت الدراسة فعالية بعض المركبات في تثبيط بعض أنواع الخلايا السرطانية في مستويات غير سامة للخلايا السليمة مما يجعل البحث في هذه المركبات مبشراً.
التقييم المخبري لنشاط عائلة مبتكرة من معقدات النحاس المرتبطة بالأمينات المتعددة في علاج خلايا السرطان في المختبر